What really matters to get to the top: an approach to relative age effect on Brazilian basketball - Oliveira, H. Z.; Ribeiro Junior, D. B.; Vianna, J. M.; Figueiredo, A. J.; Werneck, F. Z. (Journal of Physical Education, 2019)
In sport, the relative age effect (RAE) refers to a phenomenon that provides advantages of participation and performance to the athletes born in the first months of the year of selection in relation to the other athletes within the same age category. The aim of the present study was to investigate the relative age effect on Liga de Desenvolvimento do Basquete (LDB), Liga de Basquete Feminino (LBF) e Novo Basquete Brasil (NBB) considering the geographic region, the final classification of the teams and the career period of athletes. The study sample consisted of 831 athletes enrolled in the main Brazilian basketball leagues, 2014-2015 season. The information of the teams and the quarter of birth were obtained through the website of the Brazilian Basketball Confederation (www.cbb.com.br) and the website of the Brazilian National Basketball League (www.lnb.com.br). The RAE was found in the Southeast and South teams of the LDB, in the Southeast NBB teams and it was not related to the final classification of the teams. In addition, the relative age effect was reversed in the NBB athletes who were in the career consolidation stages. It is concluded that the RAE is present in the Brazilian basketball players of the LDB e NBB, with an inverse RAE being observed in the athletes from 25 to 34 years and absence of this phenomenon in those who are in the final phase of the sports career.